Variations in Hospital Admissions of Non-Communicable Disease Patients Before and During The COVID-19 Pandemic (A Tertiary Care Setting, January 2018-June 2021) - Seyma Aliye Kara; Banu Cakir (Springer, 2024)
Abstract Background This study aimed to analyze the variations (if any) in hospital admissions of patients with any of the five common non-communicable diseases (NCDs), based on secondary analysis of electronic health records of patients admitted to Hacettepe University Hospitals at least once, from January 1, 2018 through June 15, 2021. Design Data were recruited from hospital's electronic health records on patients with diagnoses of ischemic heart disease, hypertension, diabetes, cancer, and chronic obstructive pulmonary disease, using relevant ICD-10 codes. Results Compared to the corresponding time span in the pre-pandemic period, the number of hospital admissions of patients with selected five NCDs significantly decreased during the pandemic, with an official start in Turkey on March 11, 2020. Number of total-, out-patient-, and in-patient admissions of NCD patients were significantly lower in the pandemic period compared to the expected values in time series analysis, controlling for patient characteristics, and seasonality. Conclusions Study findings suggest that there has been a prominent impediment in NCD patients' access to, and/or use of health care services over the pandemic, which might evolve to higher admission rates, severity and fatality of such patients in the upcoming years. Further studies are warranted for confirmation of our findings in other care settings, with individual-based data on care compensation through settings other than regular admission sites (if any), and/or the reasons for under-use of services.